Prevalence of Symptomatic Hand Osteoarthritis and Its Impact on Functional Status among the Elderly: The Framingham Study - Zhang, Y. (American journal of epidemiology, 2002)
Osteoarthritis is one of the most common joint disorders in the elderly, yet few studies have targeted symptomatic osteoarthritis, especially symptomatic hand osteoarthritis. The authors conducted a survey in 1992-1993 among an elderly population to estimate the prevalence of symptomatic hand osteoarthritis and to assess its impact on grip strength and functional activities. Framingham Study subjects received hand radiographs and answered queries on joint symptoms. Functional activities were assessed using an interviewer-administered questionnaire. Grip strength and observed functional performance were evaluated using standard procedures. A hand joint was defined as having symptomatic osteoarthritis if both symptoms and radiographic evidence of osteoarthritis were present. Of 1,041 subjects aged 71-100 years (36% men), the prevalence of symptomatic hand osteoarthritis was higher in women (26.2%) than in men (13.4%). Compared with those without symptomatic hand osteoarthritis, subjects with the disease had 10% reduced maximal grip strength, reported more difficulty writing, handling, or fingering small objects (odds ratio = 3.4), and showed more self-reported and observed difficulty carrying a 10-pound (4.5-kg) bundle (odds ratio = 1.7 and 1.6, respectively). In conclusion, in the context of a remarkable paucity of data on the epidemiology of symptomatic hand osteoarthritis, this study suggests that symptomatic hand osteoarthritis is a common disease among elders and frequently impairs hand function.